2017
DOI: 10.1093/ofid/ofw274
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Oritavancin Relative to Vancomycin for Patients with Acute Bacterial Skin and Skin Structure Infections (ABSSSI) in the Outpatient Setting: Results From the SOLO Clinical Trials

Abstract: Background.The objective of this analysis was to evaluate the efficacy and safety of oritavancin compared with vancomycin for patients with acute bacterial skin and skin structure infections (ABSSSIs) who received treatment in the outpatient setting in the Phase 3 SOLO clinical trials.Methods.SOLO I and SOLO II were 2 identically designed comparative, multicenter, double-blind, randomized studies to evaluate the efficacy and safety of a single 1200-mg dose of intravenous (IV) oritavancin versus 7–10 days of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 14 publications
(17 reference statements)
4
18
0
Order By: Relevance
“…While the prevalence of MRSA decreased between 2011 and 2014 among 2 major hospital-acquired infections (central line-associated bloodstream infection [CLABSI] and surgical site infection [SSI]; https://gis.cdc.gov/grasp/PSA/MapView.html [ 7 ]), MRSA remains a frequent and concerning pathogen in many patient populations [ 8 ]. The predominance of this pathogen in CHROME-enrolled patients reinforces the ongoing need for anti-MRSA agents that enable patients with skin and skin structure infections to be cost-effectively managed as outpatients, without concern for poor medication compliance [ 9–11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the prevalence of MRSA decreased between 2011 and 2014 among 2 major hospital-acquired infections (central line-associated bloodstream infection [CLABSI] and surgical site infection [SSI]; https://gis.cdc.gov/grasp/PSA/MapView.html [ 7 ]), MRSA remains a frequent and concerning pathogen in many patient populations [ 8 ]. The predominance of this pathogen in CHROME-enrolled patients reinforces the ongoing need for anti-MRSA agents that enable patients with skin and skin structure infections to be cost-effectively managed as outpatients, without concern for poor medication compliance [ 9–11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were observed in a decision-analytical model [ 13 ]. The comparable efficacy and safety of oritavancin in the ambulatory setting with that observed for patients treated in the inpatient setting [ 9 ] suggests that a single 1200-mg dose of oritavancin for the treatment of skin and skin structure infection could likely replace vancomycin and beta-lactams as primary therapy in certain settings.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the results of phase III clinical trials have indicated that a single dose of oritavancin has comparable efficacy to twice-daily intravenous vancomycin for 7-10 days in the outpatient setting [14][15][16]. Oritavancin was generally well tolerated, and very few patients in the oritavancin group required subsequent care in the inpatient setting post outpatient treatment [16]. Although there are challenges to directly extrapolating real-world effectiveness outcomes from phase III trials, these data support the use of oritavancin in the outpatient setting.…”
Section: Discussionmentioning
confidence: 99%
“…There is also the potential to use oritavancin to facilitate the early discharge of a patient with a SSTI after their acute infection resolves. Despite its theoretical benefits, published data describing the real-world outcomes of patients who received oritavancin beyond its pivotal phase III clinical trials [14][15][16] are scant [17][18][19]. The purpose of this report was to describe the results of two separate multicenter observational cohort studies that examined the outcomes associated with two unique usage patterns of oritavancin.…”
Section: Key Pointsmentioning
confidence: 99%
“…Because of its singledose therapy, it has been postulated that oritavancin could be used to shift the care of appropriate ABSSSI patients from the inpatient to the outpatient setting [8]. Across the SOLO trials, 792 patients were treated solely in the outpatient setting, and very few patients in the oritavancin group (1.3%) required subsequent care in the inpatient setting post outpatient treatment [9]. More recently, data from the Clinical and Historic Registry and Orbactiv Medical Evaluation (CHROME) postmarketing registry reported that over 85% of patients were treated in an outpatient infusion center, a positive clinical response was observed in 92.8% of patients, and microbial eradication was observed in 90.0% of patients with posttherapy cultures.…”
Section: Description Of the Standard Of Care Groupmentioning
confidence: 99%